THE USE OF MACROPHYTE TYPHA LATIFOLIA FILTERS IN THE TREATMENT OF WASTEWATERS OF MEDJERDA RIVER, IN SOUK-AHRAS CITY (NORTH-EAST ALGERIA) - Mamine, N; Grara, N; Khaldi, F. (My University, 2019)
The present study was aimed to test the purifier capacities of a helophyte plant, and herein the cattail (Typha latifolia) has been used to purify the raw wastewaters through monitoring the contamination physico-chemical and parasitological indicators following various stay periods. The experimental pilot scheme is composed of three planted trays of young Typha stem. Each one was retained, respectively a treatment period of 7, 14 and 21 days. The supply of planted systems are exclusively occurred through the release of wastewaters in Medjerda river (discharge of river).The results have shown that these helophytes lead to the neutralization of pH, along with decrease in electrical conductivity of raw wastewaters. The monitoring of the purifying performances of the three systems shows that the third planted tray ensure an important elimination of the total suspended matter (TSS) at 97.6 % and the turbidity (92.4 %), which showed to be efficient in removing the organic charge with a reduction in BOD5 (90.1 %), COD (92.66 %) and the nutrients (NH4+: 88.54 % and PO43-: 91.9 %). Moreover, the concentrations of these chemicals do not exceed the national (J.O.R.A) and international (WHO, FAO) standards for the irrigation water. Regarding the parasite load, the three planted trays lead to the elimination of the total parasitic helminth eggs